Trastuzumab resistance in HER2-positive breast cancer: Mechanisms, emerging biomarkers and targeting agents - Wang, Zhen-hao; Zheng, Zhuo-qun; Jia, Shi−cheng; Liu, Shu-ni; Xiao, Xiao-fen; Chen, Guan-yuan; Liang, Wei-quan; Lu, Xiao-feng (Frontiers in Oncology, 2022)
Trastuzumab is a standard molecular targeted therapy for human epidermal growth factor receptor 2(HER2) -positive breast cancer, which can significantly improve the survival of patients with this molecular subtype of breast cancer. However, the clinical problem of onset or secondary resistance to trastuzumab has limited its efficacy. Therefore, it is very important to explore the mechanism of trastuzumab resistance and formulate countermeasures. Our study described the underlying molecular mechanism of trastuzumab resistance including ERBB2 mutations and nuclear localization, transcriptional and post-translational alterations of ERBB2, over-activation of bypass signaling pathways activation and so on. Then summarize the potential emerging predicting biomarkers and therapeutic strategies for trastuzumab resistance, in order to provide research direction for reversing trastuzumab resistance